Methods for conducting searches in healthcare reviews: A systematic review - Justin Clark; Elaine Beller; Connor Forbes; Luis Furuya-Kanamori; Sharon Sanders (Research Synthesis Methods, 2026)
Abstract The standard approach for identifying studies for reviews has remained consistent for many years. This approach can be time-consuming, with quality reliant on searcher skill. Alternate approaches aiming to improve efficiency have been proposed, but there is uncertainty around their performance. To inform searching conduct, we systematically reviewed studies comparing alternate and standard search approaches. We searched PubMed and the Library, Information Science and Technology Abstracts (LISTA) databases on 22 January 2025, browsed the Summarized Research in Information Retrieval for HTA (SuRe Info) website, reviewed reference lists of reviews and book chapters, and conducted a backwards and forwards citation search of included studies. Risk of bias (RoB) was assessed using a modified version of Quality Assessment of Diagnostic Accuracy Studies tool version 2 (QUADAS-2), and alternate approaches were categorised according to whether they potentially (1) improved search conduct, (2) worsened search conduct, or (3) had an impact that was difficult to interpret. We identified 3,520 records and included 14 studies evaluating 12 alternative search approaches. We identified four approaches that potentially improve searches, six which may make searches worse, and two with difficult to interpret results. Most studies had high or unclear RoB arising from the standard search conduct and concern regarding the applicability of the results. Searches may be improved by (1) using seed studies to design searches; (2) adding study design filters; (3) adding backwards citation searching; (4) using automation tools for translating searches across databases. More robust evaluations are needed before we can make stronger recommendations.